2012
DOI: 10.1038/ismej.2012.74
|View full text |Cite
|
Sign up to set email alerts
|

Link between microbial composition and carbon substrate-uptake preferences in a PHA-storing community

Abstract: The microbial community of a fermented molasses-fed sequencing batch reactor (SBR) operated under feast and famine conditions for production of polyhydroxyalkanoates (PHAs) was identified and quantified through a 16 S rRNA gene clone library and fluorescence in situ hybridization (FISH). The microbial enrichment was found to be composed of PHA-storing populations (84% of the microbial community), comprising members of the genera Azoarcus, Thauera and Paracoccus. The dominant PHA-storing populations ensured the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 39 publications
(43 reference statements)
7
78
0
1
Order By: Relevance
“…The impact of pH, OLR, and substrate consumption preferences was investigated by Oehmen et al (2013); Carvalho et al (2014), and Albuquerque et al (2013), respectively, using a MMC acclimatized to fermented molasses dominated by Azoarcus (63.2 %) and Thauera (25.1 %), as described by Albuquerque et al (2010). In these three works, the authors imposed cycles of 12 h, a HRT of 1 day, and a SRT of 10 days.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of pH, OLR, and substrate consumption preferences was investigated by Oehmen et al (2013); Carvalho et al (2014), and Albuquerque et al (2013), respectively, using a MMC acclimatized to fermented molasses dominated by Azoarcus (63.2 %) and Thauera (25.1 %), as described by Albuquerque et al (2010). In these three works, the authors imposed cycles of 12 h, a HRT of 1 day, and a SRT of 10 days.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…This technique also permits the identification of the microorganisms involved (Lee et al 1999), but it means an increase in the technique complexity. During the SBR cycles, Albuquerque et al (2013), using FISH, observed that 84 % of the selected MMC was constituted by Paracoccus (50 %), Azoarcus, (26 %) and Thauera (8 %). Despite different uptake rates being obtained when each carbon source was fed individually and mixed with other VFAs, MAR-FISH showed the preference for each VFA by these genera.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Este resultado faz com que a torta de tabaco possa ser utilizada como fonte de carbono para obtenção de biopolímeros como o P(3HB) produzido por microrganismos (ALBUQUERQUE et al, 2011;ALBUQUERQUE et al, 2013;REDDY et al, 2003;HAYWOOD et al, 1990;RAMACHANDRAN et al, 2007).…”
Section: Composição Centesimal Da Torta De Tabacounclassified
“…A study carried out by Albuquerque et al (2013) has shown that even when using the same profile of VFA feeding, in experiments operated under the same conditions, differences in 3HV content in the final PHBV copolymer have been observed. This phenomenon could be associated with differences in the community structure.…”
Section: Pha Synthesismentioning
confidence: 99%